T-BOT as an Effort to Overcome Speech Delay in Children - Zupri Henra; Akhmad Zulkifli (Journal of Applied Engineering and Technological Science (JAETS), 2022)
Speech is a developmental stage that begins in infancy. The speech stage must be considered as early as possible, because it can be used as a parameter or benchmark for the presence or absence of developmental disorders in children. Based on the results of the Observation and Research of Literature Studies conducted, speech delay or speech delay is a phenomenon that is often found in today's society, especially in the digital world as it is now. Based on the research obtained, parents (both father and mother) currently do not have quality time with their children because they are busy working and dominated by smartphones. Currently, there are many speech therapy practices, both opened independently by doctors and in hospitals. However, there are some parents who say that their children experience stress when they are brought to a therapy place because they feel threatened or afraid of the atmosphere in a therapy place that is foreign to them. There are studies that reveal that speech delay can also be done at home. The causes of speech delay are children who have too much screen time, are rarely invited to interact in two directions, and lack of stimulus from family or closest people. The purpose of making T-BOT or (Talking Robot) is as an effort to overcome and can be speech therapy for children from the age of 1.5 years by inputting various vocabulary, compound sentences consisting of 2 words, 3 words to 1 structured sentences. The existence of this T-BOT will be the first alternative for parents to help provide speech therapy for children at home and of course children do not feel pressured and feel more comfortable playing while practicing their speaking skills with the T-BOT. The output produced is in the form of a robot that provides information in the form of voice in Indonesian as the mother tongue of our country. The child's speech development will also be evaluated to see how effectively the T-BOT is working.